Finland - Implementing a Global Diversity Management Initiative in Finland - Smale, Adam; Björkman, Ingmar; Säntti, Risto; Sivasubramanian, Narashima Boopathi (Routledge, 2017)
Finland is the leading or near the top of many international comparisons in terms of growth and development in the economic, technological and social spheres. Despite changes in recent years, the Finnish economy remains heavily manufacturing based, led by engineering and high technology firms. Many Finnish companies are waking up to the reality that the demographic changes and related diversity management issues are the business issues. From the outset of the global workforce diversity management and inclusiveness initiative (D&I initiative), people within Petrocom Finland disagreed about the level of priority that should be given to diversity management issues. Some of these arguments were based on whether diversity management represents a critical business issue, some were based on its relevance in a workplace setting, and others were based on its relevance given Finland's and the Finnish unit's demographics. For employees, the introduction of sensitive and personal issues in discussions of D&I made typically reserved Finnish people feel noticeably uncomfortable.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|